Keratinocyte growth regulation in fibroblast cocultures via a double paracrine mechanism - Nicole Maas-Szabowski, Nicole; Shimotoyodome, Akira; Fusenig, Norbert (Journal of cell science, 1999)
Skip to Next Section - Epithelial-mesenchymal interactions play an important role in regulating tissue homeostasis and repair. For skin, the regulatory mechanisms of epidermal-dermal interactions were studied in cocultures of normal human epidermal keratinocytes (NEK) and dermal fibroblasts (HDF) rendered postmitotic by alpha-irradiation (HDFi). The expression kinetics of different cytokines and their receptors with presumed signalling function in skin were determined at the RNA and protein level in mono- and cocultured NEK and HDFi. In cocultured HDFi, mRNA and protein synthesis of keratinocyte growth factor (KGF) (FGF-7) was strongly enhanced, whereas in cocultured keratinocytes interleukin (IL)-1alpha and -1beta mRNA expression increased compared to monocultures. Thus we postulated that IL-1, which had no effect on keratinocyte proliferation, induced in fibroblasts the expression of factors stimulating keratinocyte proliferation, such as KGF. The functional significance of this reciprocal modulation was substantiated by blocking experiments. Both IL-1alpha and -1beta-neutralizing antibodies and IL-1 receptor antagonist significantly reduced keratinocyte proliferation supposedly through abrogation of KGF production, because IL-1 antibodies blocked the induced KGF production. These data indicate a regulation of keratinocyte growth by a double paracrine mechanism through release of IL-1 which induces KGF in cocultured fibroblasts. Thus IL-1, in addition to its proinflammatory function in skin, may play an essential role in regulating tissue homeostasis.